2022
DOI: 10.3934/naco.2021019
|View full text |Cite
|
Sign up to set email alerts
|

A novel methodology for portfolio selection in fuzzy multi criteria environment using risk-benefit analysis and fractional stochastic

Abstract: This article proposes an efficient approach for solving portfolio type problems. It is highly suitable to help fund allocators and decision makers to set up appropriate portfolios for investors. Stock selection is based upon the risk benefits analysis using MADM approach in fuzzy environment. This sort of analysis allows decision makers to identify the list of acceptable portfolios where they can assign some portions of their asset to them. The purpose of this article is two folds; first, to introduce a method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
0
0
Order By: Relevance
“…Several authors considered the fuzzy as well as intuitionistic fuzzy sets in PS models, for instance, Zhang et al [33], Zhou and Xu [34], Zhou et al [35], etc. Khalifa et al [36] suggested a novel solution methodology to deal with a PS problem in a fuzzy situation, where Dymova et al [37], Gong et al [38] and Mehrjerdi [39] dealt with a methodology for the PS problem using risk-benefit analysis in the fuzzy environment.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors considered the fuzzy as well as intuitionistic fuzzy sets in PS models, for instance, Zhang et al [33], Zhou and Xu [34], Zhou et al [35], etc. Khalifa et al [36] suggested a novel solution methodology to deal with a PS problem in a fuzzy situation, where Dymova et al [37], Gong et al [38] and Mehrjerdi [39] dealt with a methodology for the PS problem using risk-benefit analysis in the fuzzy environment.…”
Section: Introductionmentioning
confidence: 99%